(untitled) - Brennan, Kevin F. (New York, 2002)
The book contains many homework exercises at the end of each chapter, and a solution manual can be obtained for instructors. Emphasizing the development of new technology, Theory of Modern Electronic Semiconductor Devices is an ideal companion to electrical and computer engineering graduate level courses and an essential reference for semiconductor device engineers.
Vật lý bán dẫn
Keywords: Chất bán dẫn,Linh kiện điện tử,Semiconductors.,Transistors